The effects of Ascophyllum nodosum, Camellia sinensis-leaf extract, and their joint interventions on glycolipid and energy metabolism in obese mice - Xu, Yuhan; Jia, Xiuzhen; Zhang, Wei; Xie, Qiaoling; Zhu, Meizhen; Zhao, Zifu; Hao, Jingyu; Li, Haoqiu; Du, Jinrui; Liu, Yan; Feng, Haotian; He, Jian; et al. (Frontiers in Nutrition, 2023)
Objectives: Obesity is often associated with glucolipid and/or energy metabolism disorders. Ascophyllum nodosum extract (Seaweed extract, SE) and Camellia sinensis-Leaf extract (Tea extract, TE) have been reported to promote positive metabolic effects through different mechanisms. We investigated the effects of SE and TE on metabolic homeostasis in diet-induced obese mice and discussed their functional characteristics. Methods: Male C57BL/6J mice fed high-fat diets for 8 weeks were established as obese models and subsequently divided into different intervention groups, followed by SE, TE, and their joint interventions for 10 weeks. Body weight and food intake were monitored. Fasting glucose and oral glucose tolerance tests were interspersed during the experiment. After the intervention, the effects on obesity control were assessed based on body composition, liver pathology section, blood lipids and glucose, respiratory exchange ratio (RER), energy expenditure (EE1, EE2, EE3), inflammatory factors, lipid anabolism enzymes, and gut flora of the obese mice.Results: After continuous gavage intervention, the mice in the intervention groups exhibited lower body weight (lower about 4.93 g, vs. HFD 38.02 g), peri-testicular fat masses (lower about 0.61 g, vs. HFD 1.92 g), and perirenal fat masses (lower about 0.21 g, vs. HFD mice 0.70 g). All interventions prevented diet-induced increases in plasma levels of glucose, adiponectin, leptin, and the inflammatory factors IL-1β and TNF-. The RER was modified by the interventions, while the rhythm of RER was not. Blood lipids (total cholesterol, triglycerides, LDL) were decreased and associated with lower lipid anabolism enzymes. Besides, the SE and TE interventions altered the This is a provisional file, not the final typeset article structure and abundance of specific flora. Different interventions inhibited the growth of different genera positively associated with obesity (Escherichia-Shigella, Helicobacter, etc.) and promoted the growth of Akkermansia and Bacteroides, thus affecting the chronic inflammatory state. Conclusions: SE and TE both have synergistic effects on weight control and glucolipid metabolism regulation by improving insulin sensitivity and reducing lipid synthesis-related enzyme expression, whereas the combination of SE and TE (3:1) has a better effect on regulating energy metabolism and inhibiting chronic inflammation.